2016
DOI: 10.1038/ncomms13415
|View full text |Cite
|
Sign up to set email alerts
|

A natural light-driven inward proton pump

Abstract: Light-driven outward H+ pumps are widely distributed in nature, converting sunlight energy into proton motive force. Here we report the characterization of an oppositely directed H+ pump with a similar architecture to outward pumps. A deep-ocean marine bacterium, Parvularcula oceani, contains three rhodopsins, one of which functions as a light-driven inward H+ pump when expressed in Escherichia coli and mouse neural cells. Detailed mechanistic analyses of the purified proteins reveal that small differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
166
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(184 citation statements)
references
References 56 publications
11
166
0
7
Order By: Relevance
“…Blocking access of protons to the retinal Schiff base from the cell cytoplasm should enable preferential exchange of protons with the outside of the cell. This hypothesis is supported by a recent report that describes a natural light-driven inward proton pump showing the capacity of microbial rhodopsins to accept protons from outside the cell 22 . To block access of protons from the cytoplasmic side, we substituted the amino acid at the PD position of Voltron for a neutral residue (D92N).…”
supporting
confidence: 53%
“…Blocking access of protons to the retinal Schiff base from the cell cytoplasm should enable preferential exchange of protons with the outside of the cell. This hypothesis is supported by a recent report that describes a natural light-driven inward proton pump showing the capacity of microbial rhodopsins to accept protons from outside the cell 22 . To block access of protons from the cytoplasmic side, we substituted the amino acid at the PD position of Voltron for a neutral residue (D92N).…”
supporting
confidence: 53%
“…The widely spread presence and importance of pR-based phototrophy in the marine environment 17 was identified. Recently, rhodopsins that function as inward proton pumps were discovered 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that dinoflagellates use some unknown signaling mechanism that is compatible with mammalian protein targeting machinery. PR in dinoflagellates is highly similar to proteorhodopsin, which are globally abundant in bacteria (Béja et al 2013;Gómez-Consarnau et al 2010) and well characterized as a proton pump (Béja et al 2000;Inoue et al 2016). Since its first discovery in dinoflagellates (Lin et al 2010), eukaryotic homologs of PR have also been found in other eukaryotes microorganisms, such as diatoms, haptophytes and cryptophytes (Marchetti et al 2015), and recently found in arctic microbial eukaryotes (Vader et al 2018).…”
Section: Discussionmentioning
confidence: 99%